2018
DOI: 10.1016/j.ebiom.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal modulation of mesenchymal stem cells and tumor cells promotes lung cancer metastasis

Abstract: Metastasis is a multi-step process in which direct crosstalk between cancer cells and their microenvironment plays a key role. Here, we assessed the effect of paired tumor-associated and normal lung tissue mesenchymal stem cells (MSCs) on the growth and dissemination of primary human lung carcinoma cells isolated from the same patients. We show that the tumor microenvironment modulates MSC gene expression and identify a four-gene MSC signature that is functionally implicated in promoting metastasis. We also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 74 publications
(91 reference statements)
0
53
0
Order By: Relevance
“…In contradiction with this property, Fregni et al reported that the tumor microenvironment of MSCs implies some of the selected genes to overexpress and promotes metastasis in the case of lung cancer-derived MSCs. Here, the overexpressed genes were found out to be tumor-initiating markers and progressive towards metastasis [146]. MSCs can be miscreant due to their immune-microenvironment modulatory property, one recent example was the study of MSCs residing in the tumor microenvironment, where they developed therapy resistance in tumor cells [147].…”
Section: Outcome Of Modified Mscs: Positive and Negative Aspectsmentioning
confidence: 99%
“…In contradiction with this property, Fregni et al reported that the tumor microenvironment of MSCs implies some of the selected genes to overexpress and promotes metastasis in the case of lung cancer-derived MSCs. Here, the overexpressed genes were found out to be tumor-initiating markers and progressive towards metastasis [146]. MSCs can be miscreant due to their immune-microenvironment modulatory property, one recent example was the study of MSCs residing in the tumor microenvironment, where they developed therapy resistance in tumor cells [147].…”
Section: Outcome Of Modified Mscs: Positive and Negative Aspectsmentioning
confidence: 99%
“…Hitherto, the cellular and molecular mechanisms of MSC transition from BM-MSCs to tumor-derived MSCs have not been clearly elucidated. Accumulating evidences have indicated that cancer cells or their conditioned medium could induce the activation of MSCs to assume a tumor-promoting phenotype ( 65 , 66 ). Moreover, tumor-educated neutrophils were also reported to induce the transformation of MSCs into cancer-associated fibroblasts (CAFs), which in turn remarkably facilitated the growth and metastasis of gastric cancer ( 67 ).…”
Section: Tam-triggered Transition Of Mscs In Gastric Cancermentioning
confidence: 99%
“…To study the role of MSC on cancer development and progression, several animal models has been developed, mainly xenograft and syngenic small rodents, with MSC co-injected with tumour cells (5153). In these models, MSC participate to tumour pathophysiology, ultimately facilitating the metastatic spread of weakly metastatic cancer (52, 5456). MSC/tumour cells ratio seems to be particularly relevant like for tumour dormancy/growth, as demonstrated in melanoma or osteosarcoma models (57, 58).…”
Section: In Vivo Modelsmentioning
confidence: 99%